Answer:
A) t = (f -v)/a
Step-by-step explanation:
Undo the operations done to t, in reverse order. Here, t is multiplied by "a" then the product is added to v.
To solve for t, first you undo the addition of v by subtracting v from both sides of the equation.
f = v + at
f - v = at . . . . . subtract v
Then you undo the multiplication by "a" by dividing both sides of the equation by "a":
(f - v)/a = t . . . . . . sort of matches choice A
_____
Please note that the parentheses are required. f -v/a is something quite different. If this is typeset, the fraction bar does the grouping. If it is written in plain text, parentheses are required for grouping.
[tex]t=\dfrac{f-v}{a}[/tex]